The writings of David Thompson. - Thompson, David, 1770-1857 (Publications of the Champlain Society., 2015)
David Thompson's Travels is one of the finest early expressions of the Canadian experience. The work is not only the account of a remarkable life in the fur trade but an extended meditation on the land and Native peoples of western North America. The second in a planned three volumes of Thompson's writings, this edition completes the great surveyor and fur trader's spirited autobiographical narrative. In the 1848 Travels, Thompson describes his most enduring historical legacy - the extension of the fur trade across the Continental Divide between 1807 and 1812. During these years he established several Nor'wester trading posts, made contact with the tribal peoples of the Columbia Plateau, and tirelessly mapped the lands he traversed, all the time striving westward toward the Pacific. The tale culminates with Thompson's historic arrival at the mouth of the Columbia in July 1811. Like its companion Volume 1, this work presents an entirely new transcription by William Moreau of Thompson's manuscript, and is accompanied by an introductory essay placing the author in his historical and intellectual context. Extensive critical annotations, a biographical appendix, and historical and modern maps, make this the definitive collection of Thompson's works, and bring one of North America's most important travelers and surveyors to a new generation of readers.